PENGARUH VARIABEL MAKROEKONOMI TERHADAP JAKARTA ISLAMIC INDEX PERIODE 2011-2018 - Syafrina Hidayati; Puji Sucia Sukmaningrum (Universitas Airlangga, 2019)
This research aims to determine the effect of Macroekonomic Variables against the sharia stock index, Jakarta Islamic Index . the approach used is quantitative by using the Vector Error Correction Model (VECM) analysis technique with the STATA program.While the Inflation, Exchange Rates,Bank Indonesia Sharia Certificate, Industrial Production Index and Oil Price as dependent variables and Jakarta Islamic Index (JII) as the independent variable.Secondary data are used in this research from the official website Badan Pusat Statistik, Bank Indonesia, U.S Energy Information Administration(EIA) and yahoofinance. The result of the research shows that in the short term, Inflation, Exchange Rates,Bank Indonesia Sharia Certificate, Industrial Production Index and Oil Price have no significant influence against Jakarta Islamic Index. While in the long term, Inflation, Exchange Rates,Bank Indonesia Sharia Certificate, Industrial Production Index have signicant influence against Jakarta Islamic Index. Oil price in the long term has no significant influence against Jakarta Islamic IndexREFFERENCESAnsofino, Jolianis, Yolamalinda, & Arflindo, H. 2016. Buku Ajar Ekonometrika (pertama). Yogyakarta: deepublish.Atmadja, A. S. 1999. Inflasi Di Indonesia : Sumber-Sumber Penyebab Dan Pengendaliannya. Jurnal Akuntansi Dan Keuangan, 1(1), 54–67.Bahreisj, H. (n.d.). Hadis Shahih Al-Jamius Shahih Bukhari Muslim. Surabaya: CV. Karya Utama.Bank Indonesia. 2008. Peraturan Bank Indonesia Nomor : 10/ 11 /Pbi/2008 Tentang Sertifikat Bank Indonesia Syariah.Beik, I. S., & Fatnawati, S. W. (2014). Pengaruh Indeks Harga Saham Syariah Internasional dan Variabel Makro Ekonomi terhadap Jakarta Islamic Index. Al-Iqtishad : Journal of Islamic Economics, 6(2), 155–178.Bryman, A. 2005. Social Research Methods. New York: Oxford University.Darmadji, T. 2000. Pasar Modal di Indonesia. Jakarta: Salemba Empat.Djazuli, A. 2006. Kaidah-Kaidah Fikih: Kaidah Hukum Islam Dalam Menyelesaikan Masalah-Masalah Yang Praktis. Jakarta: Kencana.Firdausi, A. N., Fahmi, I., & Saptono, I. T. 2016. Pengaruh Indeks Harga Saham Regional ASEAN dan Variabel Makroekonomi terhadap Indeks Harga Saham Syariah Indonesia (ISSI. Al-Muzara’ah, 4(2), 76–96.Fitriany. 2012. Analisa Pengaruh Krisis Global Financial terhadap Jakarta Islamic Index ( JII ) dan Index Harga Saham Gabungan ( IHSG ). Jurnal Ekonomi & Keuangan Islam, 2(1), 1–12.Gilarso, T. 2004. Pengantar Ilmu Ekonomi Makro. Yogyakarta: Kanisius.Gujarati, D. N. 2003. Ekonometrika Dasar. Jakarta: Erlangga.Gumilang, R. C., Hidayat, R. R., & Wi, M. G. 2014. Pengaruh Variabel Makro Ekonomi, Harga Emas Dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan (Studi Pada Bursa Efek Indonesia Periode 2009-2013), 14(2), 1–9.Hartono, J. 2010. Teori Portofolio dan Analisis Investasi. Yogyakarta: BPFE.Hendro, T., & Rahardja, C. T. 2014. Bank & Institusi Keuangan Non Bank di Indonesia. Yogyakarta: UPP STIM YKPN.Johar, A. 1999. Kamus Istilah Pasar Modal, Akuntansi Keuangan dan Perbankan. Jakarta: Gramedia.Karim, A. A. 2007. Ekonomi Makro Islami(ketiga). Jakarta: PT Raja Grafindo Persada.Kasiram, H. M. 2008. Metodologi Penelitian Kualitatif-Kuantitatif. Malang: UIN Malang Press.Kewal, S. S. 2012. Pengaruh Inflasi, Suku Bunga, Kurs, dan Pertumbuhan PDB Terhadap Indeks Harga Saham Gabungan. Jurnal Economia, 8(1), 53–64.Larasati, M. (2017). Pengaruh Sertifikat Bank Indonesia Syariah (SBIS), Dow Jones Islamic Market Index (DJIMI), Kurs Rupiah, dan Inflasi terhadap Jakarta Islamic Index. Universitas Muhammadiyah Yogyakarta.Mankiw, G. N. 2006. Pengantar Ekonomi Makro(Ketiga). Jakarta: Salemba Empat.Manullang, J. H. 2009. Perkembangan Indeks Produksi Industri Besar dan Sedang 2006-2009. Jakarta: BPS.Maski, G., & Widyastuti, Y. En. 2003. Efektivitas Kebijakan Suku Bunga Dalam Mencapai Keseimbangan Nilai Tukar. Tema, 4(1).Mulyani, N. (2014). Analisis Pengaruh Inflasi, Suku Bunga, Nilai Tukar Rupiah, dan Produk Domestik Bruto Terhadap Jakarta Islamic Index., 1(10).Nisa, N. K., & Sukmana, R. 2017. Analisis Pengaruh Variabel – Variabel Makroekonomi Terhadap Jakarta Islamic Indeks (JII) Periode 2007-2015. Jurnal Ekonomi Syariah Teori Dan Terapan, 4(6 Juni 2017), 449–463.Nizar, M. A. 2012. Dampak Fluktuasi Harga Minyak Dunia terhadap Perekonomian Indonesia. Buletin Ilmiah Litbang Perdagangan, 6(2), 189–209.Nurdin. 1999. Analisis Pengaruh Inflasi, Nilai Tukar, Tingkat Suku Bunga, Pertumbuhan Ekonomi, Kebijakan Pemerintah, Struktur Modal, Struktur Aktiva, Liquiditas terhadap Risiko Investasi Saham Properti di Bursa Efek Jakarta. Universitas Diponegoro.Perdana, A. R. 2008. Faktor yang Mempengaruhi Perkembangan Saham Syariah Di Jakarta Islamic Index ( JII ). Universitas Islam Negeri Syarif Hidayatullah.Pribadi, A. K. 2018. Pengaruh Harga Minyak Dunia terhadap Indeks Saham Sektoral di Indonesia. Universitas Airlangga.Putri, A. 2018. Analisis Pengaruh Variabel Makroekonomi terhadap Perkembangan Indeks Saham Syariah Indonesia (ISSI). Institut Pertanian Bogor.Ryandono, M. N. H. 2009. Bursa Efek dan Investasi Syariah. Jakarta: Serambi.Sahria. 2010. Pemodelan Sertifikat Bank Indonesia Syariah dengan Metode System Dynamics. Universitas Islam Negeri Syarif Hidayatullah.Sarwar, A., Aftab, M. H., Khan, R. A., & Qureshi, H. A. 2014. Impact of Macroeconomic Factors on the Stock Index : A Case Study of Pakistan. Sci.Int.(Lahore),26(5), 2595–2601.Sjahdeini, S. R. 2014. Perbankan Syariah. Jakarta: Kencana.Soemitra, A. 2009. Bank dan Lembaga Keuangan Syariah (Pertama). Jakarta: Kencana.Suciningtias, S. A., & Khoiroh, R. 2015. Analisis Dampak Variabel Makro Ekonomi Terhadap Indeks Saham Syariah Indonesia. Conference In Business, Accounting Anda Management, 2, 398–412.Sugiyono. 2013. Metode Penelitian Kuantitatif Kualitatif dan R & D. Bandung: Alfabeta.Sujarweni, V. W. 2015. Metodologi Penelitian Bisnis & Ekonomi(Pertama). Yogyakarta: Pustaka Baru Press.Sutedi, A. 2011. Good Corporate Governance (Pertama). Jakarta: Sinar Grafika.Syakir Sula, M. 2004. Asuransi Syariah : Konsep dan Sistem Operasional. Jakarta: Gema Insani.Tandelilin, E. 2010. Portofolio dan Investasi Teori dan Aplikasi(Pertama). Yogyakarta: Kanisius.Triyono. 2008. Analisis Perubahan Kurs Rupiah Terhadap Dollar Amerika. Jurnal Ekonomi Pembangunan, 9(2), 156–167.Zubaidah, N., & Ulum, A. S. 2015. Analisis Risiko Pembiayaan Syariah pada Sektor Ekonomi. Jurnal Kompilek, 7(2), 110–122.